Socialization of Applied Business Models at Catering Hangout Depok: Sosialisasi Terapan Business Model Di Catering Hangout Depok - Masri Pradipto; Mohammad Riski Borman; Sri Hartini; Tri Novita Sari; Adinda Farhana; Uki Aulia Rosalina (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2026)
Micro, Small, and Medium Enterprises (MSMEs) Catering Hangout is a culinary business engaged in catering services and is located in Tanah Baru Village, Beji District, Depok City, West Java. This business began operating in 2018. The main activities carried out include processing food ingredients from raw to ready-to-eat dishes. Increasingly intense competitive conditions require every business actor to be more active in attracting customers in order to expand the market. One of the challenges faced by Catering Hangout is the limited understanding of innovation in business development. Therefore, this community service activity raised the theme of socializing business concepts and strategies using the Business Model Canvas (BMC) approach as an effort to overcome this problem. BMC itself is a management framework used to design business strategies by mapping nine main elements, namely value, distribution, relationships, revenue streams, resources, activities, key partners, and cost structures. In its application to the SME Catering Hangout, the BMC approach is supported by qualitative methods through Focus Group Discussions (FGDs) and problem-solving to produce a business model design that suits the business conditions. With the socialization of BMC, it is hoped that Catering Hangout can begin to implement the 9 BMC blocks to increase sales and distribution of its products, which will have a significant impact on the company's overall turnover.